STRATEGY FOR DEVELOPING LOCAL CONTENT OF DISASTER EDUCATION IN ELEMENTARY SCHOOLS - Sutinah, Sutinah; Aji, Styo Mahendra Wasita; Aziz, Abdul (Proceedings Series of Educational Studies, 2024)
This paper aims to describe the development of local content education for disasters. Disaster risk reduction must be developed through various strategies, including formal education, as early as possible. This article was written using the literature review method. Researchers collect data from literature and documents from various literary sources such as Government regulations, relevant articles, and books. Data analysis with qualitative descriptive. The data are presented qualitatively based on the study focus pattern. This study focuses on expected disaster education, local content and disaster education, development of disaster local content education, and implementation strategies of disaster local content education. Disaster education should ideally be implemented as early as possible, starting the first formal education in elementary school. The position of local content opens up opportunities for disaster education in elementary schools through the uniqueness of the region. The development of local content of disaster education contains: education environmental insight, disaster risk reduction education programs, and disaster moral response. The five steps of the implementation strategy are curriculum development, teacher training, limited trials, extensive trials, and evaluations. Eventually, the development of local content of disaster education has the potential to develop students' resilience to disasters.